Performance Evaluation of Layered Cell Structures for 5G Networks Using Simulation-Based Analysis - Yaser, Muhammad (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The rapid growth in the use of data-driven mobile devices such as smartphones, tablets, and other connected terminals has significantly increased the demand for high-speed mobile data services. To address this challenge, 5G networks must adopt more efficient architectural strategies. This paper presents a design study of 5G cellular networks based on a layered cell structure, focusing on both theoretical analysis and computer-based simulations. A traditional single-layer cell is restructured into two-layer and three-layer configurations to evaluate the impact of layering on network performance. User devices are randomly distributed within the coverage area and connected to a central 5G base station. The simulation results, supported by theoretical modeling, demonstrate that layered cell architectures offer notable improvements in data capacity compared to the single-layer design. Among the scenarios tested, the three-layer structure achieves the highest performance, reaching up to 39,78 Mbps. These results provide valuable insights for the development and optimization of layered architectures in next-generation 5G cellular networks